Various sloped wall effect on Silicon on Insulator (SOI) phase modulator - Bidin, Mardiana; Shaari, Sahbudin; Menon, P Susthitha; Abdul Razak, Hanim; Haroon, Hazura; Arsad, Norhana; Abdullah, Huda (American Scientific Publishers, 2013)
This paper highlights the study of carrier injection effect on silicon-on-insulator phase modulator with various sloped wall waveguide structure. By default, the sloped angle 54.74° arises from anisotropic chemical etching with the waveguide aligned to the 〈111〉 crystal direction. However, etched surfaces cannot be consistent depending on many variables such as reaction temperature and etchant concentration. Therefore, different possible angles are studied in this report. The characterization of the phase modulator was carried out by 2D Silvaco CAD software under different applied voltages. The n + p + n + structure was employed to study the device performance in terms of modulation efficiency and absorption.